Clinical characteristics in two patients with partial lipodystrophy and Type A insulin resistance syndrome due to a novel heterozygous missense mutation in the insulin receptor gene. (June 2019) - Iwanishi, Masanori; Kusakabe, Toru; Azuma, Choka; Tezuka, Yuji; Yamamoto, Yukako; Ito-Kobayashi, Jun; Washiyama, Miki; Morimoto, Mayumi; Ebihara, Ken
Highlights: We have experienced two cases of a 12-year-old girl and her mother with partial lipodystrophy and a novel heterozygous missense mutation (Asn 1137  → Lys 1137 ) in the insulin receptor gene. We thought that fat loss in the proband might be caused by insulin receptor dysfunction. To the best of our knowledge, this is the first report describing clinical the clinical characteristics in patients with lipodystrophy and Type A IRS due to a heterozygous missense mutation in the insulin receptor gene. Abstract: Aims: The present report aimed to clarify the clinical characteristics in a girl at the age of 12 and her mother with partial lipodystrophy and Type A insulin resistance syndrome. Methods: We examined fat distribution in the patients using dual-energy X-ray absorptiometry, magnetic resonance imaging, and computed tomography. We performed genetic analysis to examine the causal gene for lipodystrophy and insulin resistance. Results: Both patients had partial lipodystrophy and a novel heterozygous missense mutation (Asn 1137  → Lys 1137 ) in the insulin receptor gene. Because Asn 1137 in the catalytic loop is conserved in all protein kinases, this mutation was thought to impair insulin receptor function. By whole-exome sequencing, we found the proband had neither mutations in candidate genes known to be associated with familial partial lipodystrophy nor novel likely candidate causal genes. Taken together, we thought that fat loss in these two patients might be caused by insulin receptor dysfunction. The proband had amenorrhea due to polycystic ovary syndrome. Her menstruation improved, as fat loss was restored during adolescence. This might be caused by improving insulin resistance due to increased levels of leptin and fat mass. Conclusions: This case might help to understand the mechanisms insulin receptor dysfunction that cause lipodystrophy.